App development in a sports science setting: A systematic review and lessons learned from an exemplary setting to generate recommendations for the app development process - Barisch-Fritz, Bettina; Nigg, Claudio R.; Barisch, Marc; Woll, Alexander (Frontiers in Sports and Active Living, 2023)
The digital health sector is rapidly growing. With only 4% of publishers out of academic settings, it is underrepresented in app development. The objective of this study is to assess the current state of app development with a systematic review and a survey within an exemplary academic setting along the following research questions: (Q1) Are software engineering principles sufficiently known in the sports science app development context? (Q2) Is the role of sports scientists in the context of app development sufficiently understood? The systematic review was conducted by two independent reviewers within the databases Pubmed, Scopus, Web of Science, and IEEE Xplore. The PICO schema was used to identify the search term. We subtracted information about five main topics: development process, functional requirements and features, security, technology, and dissemination. The survey was developed by a multidisciplinary team and focused on the five main topics. Out of 701 matches, 21 were included in the review. The development process was only described in seven studies. Functional requirements and features were considered in eleven studies, security in three, technology in 13, and dissemination in twelve with varying details, respectively. Twelve respondents (mean age 33(7) years, 58% female) replied to the survey. The survey revealed limited knowledge in realization of security measures, underlying technology and source code management, and within dissemination. Respondents were able to provide input on development process as well as functional requirements and features. The involvement of domain experts is given in seven studies of the review and described in two more. In 50% of survey respondents the role in app development is defined as research assistant. We conclude that there is a varying degree of software engineering knowledge in the sports science app development context (Q1). Furthermore, we found that the role of sports scientists within app development is not sufficiently defined (Q2). We present recommendations for improving success probability and sustainability of app development and give orientation on potential roles of sports scientists as domain experts. Future research should focus on the generalizability of these findings and the reporting of the app development process.